2020
DOI: 10.1136/bmjopen-2020-044197
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous communities’ responses to the COVID-19 pandemic and consequences for maternal and neonatal health in remote Peruvian Amazon: a qualitative study based on routine programme supervision

Abstract: AimTo explore indigenous communities’ responses to the COVID-19 pandemic and its consequences for maternal and neonatal health (MNH) care in the Peruvian Amazon.MethodsMamás del Río is a community-based, MNH programme with comprehensive supervision covering monthly meetings with community health workers (CHW), community leaders and health facilities. With the onset of the lockdown, supervisors made telephone calls to discuss measures against COVID-19, governmental support, CHW activities in communities and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 26 publications
0
45
0
3
Order By: Relevance
“…This finding is consistent with the study done in Remote Peruvian Amazon revealed that almost all communities instigated rules prohibiting entry of non-residents, including family members, social isolation, exit restriction, social distance within the community and avoid physical contact for the purpose of prevention mechanism of COVID – 19 infection. 14 Similarly, a different qualitative research reviews supported this finding. 15 …”
Section: Discussionmentioning
confidence: 78%
“…This finding is consistent with the study done in Remote Peruvian Amazon revealed that almost all communities instigated rules prohibiting entry of non-residents, including family members, social isolation, exit restriction, social distance within the community and avoid physical contact for the purpose of prevention mechanism of COVID – 19 infection. 14 Similarly, a different qualitative research reviews supported this finding. 15 …”
Section: Discussionmentioning
confidence: 78%
“…However, in countries such as Bolivia ( Fondo para el Desarrollo de los Pueblos Indígenas de América Latina y el Caribe, 2020a ), Peru ( Centro Nacional de Epidemiología Prevención y Control de Enfermedades, 2021 ), Ecuador ( Castro, 2020 ), Venezuela ( Pan American Health Organization, 2021b ), and Colombia ( Organización Panamericana de la Salud, 2020 ), cases of COVID-19 have been reported in the indigenous populations. During the COVID-19 pandemic, a deficit of diagnostic tests, lack of masks, and the suspension of health programs in indigenous communities have been described ( Reinders et al, 2020 ), being a situation that could lead to a decline in health care in these communities as well as an underestimation of the prevalence of COVID-19 in indigenous populations. Thus, health care for this historically vulnerable group should be prioritized during times of crisis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in Peru, it has been described that the majority of the communities of the rural districts Nauta, Parinari, and Sequena prohibited the entry of people not belonging to the community. However, half of these communities did allow residents to travel to the cities for commercial and social reasons, and the prohibition of social events was only abided by a third of the communities since the control measure, decreed by the Peruvian government, competes with their daily routine ( Reinders et al, 2020 ). Although it is described that the measures taken by governments to control the spread of COVID-19 towards indigenous communities have been deficient ( Fondo para el Desarrollo de los Pueblos Indígenas de América Latina y el Caribe, 2020b ), it should be emphasized that mistrust in authority and disbelief in the existence and severity of the pandemic likely influenced outcomes ( Fondo para el Desarrollo de los Pueblos Indígenas de América Latina y el Caribe, 2020b ; Meneses-Navarro et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Empowered with a tablet application, the community health workers conduct home visits to pregnant women and their families, deliver health educational content and gather data to share with local government. 5 During COVID-19 travel restrictions, the communities in the implementation area became isolated and health facilities suspended routine services. The programme rapidly adapted to meet the needs of local people, including delivery of materials and equipment for basic COVID-19 prevention, managing misconceptions through phone supervisions, developing video training for community health workers about COVID-19 and continuing home visits for people with COVID-19 symptoms.…”
Section: Community Mobilisation In Perumentioning
confidence: 99%